1989
DOI: 10.1179/mst.1989.5.8.734
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alloy additions on oxidation

Abstract: Some of the i~portant principles of alloy oxidation are discussed, with emphasis on the formatIOn of protective Cr 2 0 J , AI 2 0 J , and Si0 2 scales on iron and nickel base alloys. The competition between internal and external oxidation is consid~red and it is sho~n how establishment of the protective layer is influenced by va~lOus. p'ar~meters, Including alloy interdiffusion coefficient, oxygen solubility and~iffUSlVltym the alloy, and the relative growth rates of the various oxides. The lmportance of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Irving et al found that a protective alumina scale can be formed when Al concentration 24 at.% at 1173 K is reached. Comparable minimum Al concentrations required to form the external alumina scale were also found for the Ni-Al and Fe-Al alloys [89].…”
Section: Oxidation Behaviormentioning
confidence: 65%
See 1 more Smart Citation
“…Irving et al found that a protective alumina scale can be formed when Al concentration 24 at.% at 1173 K is reached. Comparable minimum Al concentrations required to form the external alumina scale were also found for the Ni-Al and Fe-Al alloys [89].…”
Section: Oxidation Behaviormentioning
confidence: 65%
“…13, x FOR PEER REVIEW 12 of 18minimum Al concentrations required to form the external alumina scale were also found for the Ni-Al and Fe-Al alloys[89].…”
mentioning
confidence: 71%
“…Silica acts here as a diffusion barrier and reduces therefore the cation diffusion rate through the oxide [12,33,[35][36][37]. Since silica forms fairly slowly [38,39], the establishment of a continuous layer is a lot more difficult under the fast growing pits than elsewhere. Actually, even after 200 h, a continuous healing layer was still not fully established in Diesel at 850°C.…”
Section: Effect Of Simentioning
confidence: 99%
“…The presence of Cr, Si, as well as Al, is known to improve steels corrosion resistance. Al as minor alloying element in steels have been shown to enhance corrosion resistance [11,12] The following sections discuss the materials selection for the DELTA loop test matrix, as well as corrosion specimen loading in a redesigned holder that allows high LBE velocity and more specimens simultaneous testing. As mentioned previously, Section 3 will describe corrosion specimen preparation and loading.…”
Section: List Of Figuresmentioning
confidence: 99%